2015
DOI: 10.1097/hjh.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effect of serum 25-hydroxyvitamin D levels and CYP1A1, CYP1B1 polymorphisms on blood pressure in an elderly population

Abstract: Genetic variations in CYP1A1 and CYP1B1 and the serum levels of 25(OH)D showed synergistic effect on BP, especially in individuals currently in treatment for hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…There is evidence linking CYP17 polymorphisms and estrogen synthesis variability which in turn may increase the risk for cancer [6,7,25], osteoporosis [26], Alzheimer disease [27], and also cardiovascular disease through the atherogenic process [28][29][30]; our data adds to the prior, however linking for the first time the studied CYP polymorphism with the intensity of mood symptoms in postmenopausal women. Clearly, all these conditions are steroid hormone and age-related in which genetic background may have a pivotal role over disease development and outcomes.…”
Section: Discussionsupporting
confidence: 47%
“…There is evidence linking CYP17 polymorphisms and estrogen synthesis variability which in turn may increase the risk for cancer [6,7,25], osteoporosis [26], Alzheimer disease [27], and also cardiovascular disease through the atherogenic process [28][29][30]; our data adds to the prior, however linking for the first time the studied CYP polymorphism with the intensity of mood symptoms in postmenopausal women. Clearly, all these conditions are steroid hormone and age-related in which genetic background may have a pivotal role over disease development and outcomes.…”
Section: Discussionsupporting
confidence: 47%
“…Recent studies have shown an association between BP circulating levels of 25(OH)D 28 as well as with genetic variations in CYP1A1 and CYP1B1. 29 While both studies have shown an association of 25(OH)D with systolic and diastolic BP, a stronger correlation was seen between 25(OH)D and diastolic BP. These findings need to be further explored in a prospective longitudinal study.…”
Section: Raas Blockade Increases S-klotho Levelsmentioning
confidence: 95%
“…Many observational studies have reported an inverse association between low VitD levels and brachial BP in large samples from the general population [23,24,25], but also among Peruvian adolescents [26], middle-aged individuals [27], people aged >60 years and the elderly [28,29], pregnant women and women aged 20-80 years [30,31]. Similarly, the evidence from medium to large observational studies shows strong and independent inverse associations between serum VitD and cfPWV among diverse study populations [32,33,34,35,36,37,38].…”
Section: Summary Of Observational Data On the Relationship Between Sementioning
confidence: 99%